Tata Kelola Anggaran Digital Berbasis ARKAS untuk Penguatan Akuntabilitas Publik dan Manajemen Sekolah Berorientasi Maqāṣid - Merita Diana; Safitri Agustina; Undang Rosidin (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This study is motivated by the increasing need for transparent, accountable, and educationally meaningful digital budget governance in the management of BOSP funds through ARKAS. This study aims to analyze how ARKAS-based digital budget governance shapes public accountability practices and supports maqāṣid-oriented school management. A qualitative approach with a multiple-case study design was employed in three public junior secondary schools that actively used ARKAS for budget planning, realization, and reporting. Data were collected through semi-structured interviews with principals, school treasurers, and supervisors, as well as document analysis of RKAS/ARKAS records, budget realization reports, supervision notes, and relevant policy documents. The data were analyzed thematically through coding, categorization, and theme development. The findings reveal that ARKAS functions as a digital budget governance instrument that standardizes expenditure classification, strengthens the traceability between planning and realization, improves procedural compliance, and encourages schools to allocate budgets to components more closely related to learning needs. The findings also show that ARKAS provides opportunities to integrate maqāṣid values into school management by strengthening educational benefit, fairness in resource allocation, and commitment to improving the quality of learning services. However, the optimal use of ARKAS is still influenced by users’ digital literacy, understanding of performance-based budgeting, and the quality of supervisory assistance. The implication of this study is that ARKAS should not be positioned merely as an administrative reporting application, but as a strategic instrument for developing transparent, accountable, data-based, and educationally meaningful school budget governance.